Microscope-mode imaging mass spectrometry with the PImMS camera - Halford, E (2016)
Until recently, the use of microscope-mode imaging mass spectrometry (MSI) was restricted by the available technology. Fast cameras were limited to acquiring a single image relating to a set m/z range which had to be predeﬁned before the experiment was started. Now, new developments in camera technology have produced time-stamping cameras that can record the arrival time of ions at a detector, without the need to deﬁne an exposure time. This allows the images relating to diﬀerent species with a range of m/z to be acquired simultaneously. One of these cameras is the Pixel Imaging Mass Spectrometry (PImMS) camera, which has the added advantage that each pixel within the sensor has four memory registers. This means that up to four events can be observed, by each pixel, within a single time-of-ﬂight cycle. Here, the application of the PImMS camera to microscope-mode MSI is presented. Initial experiments are conducted using a converted conventional velocity-map imaging instrument. Simulations are presented in order to predict the performance of the ion optics when used for spatial imaging, and the result of these simulations is then compared to those obtained experimentally, using a commercially available charge-coupled device (CCD) camera and a photomultiplier tube (PMT). These spatial resolutions along with simultaneously obtained mass resolutions are then compared to those obtained using a PImMS1 camera. Further experiments are presented in which the PImMS1 camera is used in conjunction with a modiﬁed commercially available mass spectrometer, the LT2 Plus (produced by Scientiﬁc Analysis Instruments Ltd — SAI). This instrument is designed to obtain isotopic resolution for m/z < 1000, whilst also maintaining a spatial resolution better than 50µm. These speciﬁcations are obtained using the PImMS1 camera, and it is shown that images of multiple chemical species can be obtained simultaneously. A new data analysis method is developed, which attempts to model the shape of PImMS data event clusters. Although the application of this method cannot be fully realised with data obtained with a PImMS1 camera, a modiﬁed version is successfully applied to PImMS1 data and produces both an improvement in the time precision of the camera, as well as a more eﬃcient use of the available data. Finally, various designs for a primary ion beam are presented that could be used in place of the standard laser desorption system. The ion beam is designed for use with an MSI instrument, ablating sample from a large area of sample, and with a short pulse length for time-of-ﬂight analysis. A ﬁnal design is presented that can produce beam pulse that can be focussed down to form a pulse length of 5ns, across a target of 2.5mm. As a collection, the works detailed in this thesis present the development of a stigmatic ion microscope that uses the PImMS camera, from a proof-of-concept to a viable analytical instrument.